EVALUASI PERENCANAAN STRUKTUR ATAS PADA PELAKSANAAN PEMBANGUNAN MASJID JAMI’ MANDIANGINKOTA BUKITTINGGI - Aprikardo, Erix; Masril, Masril; Susanti Yusman, Ana (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2023)
The planning for the construction of the Jami' Mandiangin mosque starts from the planning of the lower structure to the upper structure. In the formulation of the problem, the researcher only calculates the maximum load borne by the building, both dead load, live load and earthquake load and to know the dimensions of the structural elements and the amount of structural reinforcement needed. The research methodology is divided into two types, namely quantitative methods and qualitative methods. The study used SAP2000 to analyze the structural design to determine the magnitude of the load carried on the construction of a structural building that refers to SNI 2019. The results of the study obtained the dimensions of a circular column with a diameter of 600 mm, a column height of 4500 mm with a lot of reinforcement 17D19. Beam B1 is 450x900 mm with lots of 20D19 reinforcement. Beam B2 is 300x600 mm with a lot of 12D19 reinforcement. Beam B3 is 250x450 mm with lots of 8D19 reinforcement. The floor slab uses 10 - 200 mm in two layers with a floor slab thickness of 12 mm. From the results of the study, it was concluded that the calculation of the structure plays an important role in the construction of the structure so that it can produce a strong and sturdy building.